Analisis Implementasi 10P Dalam Bedside Handover di Ruang Rawat Inap Rumah Sakit X - Evi Setyowati; Hanny Handiyani; Hening Pujasari; Joan Xaveria Mahulae (Universitas Malahayati, 2026)
ABSTRACT The implementation of bedside handover in the inpatient room is not optimal, which may pose a risk to patient safety and satisfaction. This final scientific work aims to describe and analyze the implementation of bedside handover in the inpatient room of Hospital X, with a focus on the 10P model (patient identification, patient comfort, personal and environmental hygiene, personal diet, potty and pee, patient safety, position, puncture and pump, plan and partnership, prayer and spiritual support). This final scientific work of nurses uses observation, interview and documentation methods of bedside handover practices carried out for two weeks / 24 observations. The results showed that implementation compliance was good, namely patient identification, personal and environmental hygiene, personal diet, patient safety, puncture and pump had reached 75% / more than the average of 66.67%. Meanwhile, patient comfort, potty and pee, position, plan and partnership, prayer and spiritual support need to be developed because they are still below the average. Elements of bedside handover that are not optimal are expected to be further improved through re-socialization of SPO and optimization of supervision. Keywords: Bedside Handover, Patient Safety. ABSTRAK Pelaksanaan bedside handover di ruang rawat inap belum optimal sehingga dapat berisiko pada keselamatan pasien serta kepuasan. Karya ilmiah akhir ners ini bertujuan untuk menggambarkan serta menganalisis penerapan bedside handover di ruang rawat inap Rumah Sakit X, dengan fokus pada model 10P (patient identification, patient comfort, personal and environmental hygiene, personal diet, potty and pee, patient safety, position, puncture and pump, plan and partnership, pray and spiritual support). Karya ilmiah akhir ners ini menggunakan metode observasi, wawancara dan dokumentasi praktik bedside handover yang dilakukan selama dua minggu/ 24 pengamatan. Hasilnya menunjukkan bahwa kepatuhan pelaksanaan sudah baik yaitu patient identification, personal and environmental hygiene, personal diet, patient safety, puncture and pump sudah mencapai 75 %/ lebih dari rata rata 66,67 %. Sedangkan yang perlu dikembangkan patient comfort, potty and pee, position, plan and partnership, pray and spiritual support karena masih di bawah rata rata. Elemen bedside handover yang belum optimal diharapkan dapat lebih ditingkatkan melalui sosialisasi kembali SPO dan optimalisasi supervisi. Kata Kunci: Bedside Handover, Keselamatan Pasien.